Inhibition of STING-mediated type I IFN signaling by African swine fever virus DP71L - Lakmal Ranathunga; Sachini Abesinghe; Ji-Won Cha; Niranjan Dodantenna; Kiramage Chathuranga; Asela Weerawardhana; D. K. Haluwana; Nuwan Gamage; Jong-Soo Lee (Veterinary Research)
Abstract African swine fever virus (ASFV) is nucleocytoplasmic large DNA arbovirus and encodes many proteins involved in the interaction with host molecules to evade antiviral immune responses. Especially, evasion strategies of type I interferon (IFN-I)-mediated immune responses are crucial for early ASFV replication. However, there is still a lack of information regarding the immune evasion mechanism of ASFV proteins. Here, we demonstrated that ASFV DP71L suppresses STING-mediated antiviral responses. The conserved phosphatase 1 (PP1) motif of DP71L specifically interact with the C-terminal tail (CTT) of STING and in particular, amino acids P371, L374, and R375 of STING were important for interaction with DP71L. Consequently, this interaction disrupted the binding between STING and TANK-binding kinase 1 (TBK1), thereby inhibiting downstream signaling including phosphorylation of TBK1, STING and IRF3 for antiviral signaling. DP71L significantly interfered with viral DNA induced interferon production and IFN-mediated downstream signaling in vitro. Consistently, knockdown of DP71L enhanced antiviral gene expression in ASFV-infected cells. Taken together, these results highlight the important role of DP71L with respect to inhibition of interferon responses and provide guidance for a better understanding of ASFV pathogenesis and the development of live attenuated ASFV vaccines.